(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, a Gould-Hopper-based generalization of Fubini polynomials which are referred to as the Gould-Hopper-based bivariate Fubini polynomials were introduced. Also, properties such as addition formula, explicit formula, implicit formula, recurrence formula and symmetric identities are obtained. Moreover, some relations between the Gould-Hopper-based bivariate Fubini polynomials and some of the other special polynomials and numbers, such as the 2-variable Gould-Hopper polynomials and the Stirling number of the second kind were investigated.